2022
DOI: 10.1111/coa.13931
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in children receiving treatment for Mycobacterium abscessus otomastoiditis

Abstract: Mycobacterium abscessus (M. abscessus) is a rapidly growing nontuberculous mycobacterium (NTM), often dubbed the 'antibiotic nightmare' for its extensive resistance to antibiotics. 1 Pulmonary infections, skin and soft tissue infections are its most frequent clinical manifestations, but otomastoiditis is also an established clinical entity. 2 Treatment is difficult due to the multidrug resistance and lack of international consensus on therapeutic options as well as duration of treatment.A previous study at our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…According to recent literature, in patients with M. abscessus otomastoiditis, quality of life may temporarily be poor due to treatment. Hearing loss with adverse events such as nausea and vomiting may be noted after antibiotic treatment or surgery [22]. In the cases investigated in our study, no obvious sequelae were observed during long-term follow-up after proper management.…”
Section: Discussionmentioning
confidence: 51%
“…According to recent literature, in patients with M. abscessus otomastoiditis, quality of life may temporarily be poor due to treatment. Hearing loss with adverse events such as nausea and vomiting may be noted after antibiotic treatment or surgery [22]. In the cases investigated in our study, no obvious sequelae were observed during long-term follow-up after proper management.…”
Section: Discussionmentioning
confidence: 51%